Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given equation [tex]\( 64 = 32^{x+1} \)[/tex], let's follow a step-by-step approach:
1. Rewrite the bases in terms of powers of 2:
- Notice that [tex]\( 32 \)[/tex] can be written as [tex]\( 2^5 \)[/tex].
- Also, [tex]\( 64 \)[/tex] can be written as [tex]\( 2^6 \)[/tex].
2. Express [tex]\( 32^{x+1} \)[/tex] in terms of base 2:
- Given [tex]\( 32 = 2^5 \)[/tex], it follows that [tex]\( 32^{x+1} = (2^5)^{x+1} \)[/tex].
- Using the property of exponents [tex]\((a^m)^n = a^{mn}\)[/tex], we get:
[tex]\[ (2^5)^{x+1} = 2^{5(x+1)}. \][/tex]
3. Rewrite the equation using these expressions:
- Now the equation [tex]\( 64 = 32^{x+1} \)[/tex] becomes:
[tex]\[ 2^6 = 2^{5(x+1)}. \][/tex]
4. Set the exponents equal:
- Since the bases (2) are the same, we can equate the exponents:
[tex]\[ 6 = 5(x+1). \][/tex]
5. Solve for [tex]\( x \)[/tex]:
- First, distribute the 5 on the right-hand side:
[tex]\[ 6 = 5x + 5. \][/tex]
- Next, subtract 5 from both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 6 - 5 = 5x. \][/tex]
[tex]\[ 1 = 5x. \][/tex]
- Finally, divide both sides by 5 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{1}{5}. \][/tex]
Thus, the solution is:
[tex]\[ x = 0.2. \][/tex]
1. Rewrite the bases in terms of powers of 2:
- Notice that [tex]\( 32 \)[/tex] can be written as [tex]\( 2^5 \)[/tex].
- Also, [tex]\( 64 \)[/tex] can be written as [tex]\( 2^6 \)[/tex].
2. Express [tex]\( 32^{x+1} \)[/tex] in terms of base 2:
- Given [tex]\( 32 = 2^5 \)[/tex], it follows that [tex]\( 32^{x+1} = (2^5)^{x+1} \)[/tex].
- Using the property of exponents [tex]\((a^m)^n = a^{mn}\)[/tex], we get:
[tex]\[ (2^5)^{x+1} = 2^{5(x+1)}. \][/tex]
3. Rewrite the equation using these expressions:
- Now the equation [tex]\( 64 = 32^{x+1} \)[/tex] becomes:
[tex]\[ 2^6 = 2^{5(x+1)}. \][/tex]
4. Set the exponents equal:
- Since the bases (2) are the same, we can equate the exponents:
[tex]\[ 6 = 5(x+1). \][/tex]
5. Solve for [tex]\( x \)[/tex]:
- First, distribute the 5 on the right-hand side:
[tex]\[ 6 = 5x + 5. \][/tex]
- Next, subtract 5 from both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 6 - 5 = 5x. \][/tex]
[tex]\[ 1 = 5x. \][/tex]
- Finally, divide both sides by 5 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{1}{5}. \][/tex]
Thus, the solution is:
[tex]\[ x = 0.2. \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.